If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + (-3) = 8 -1x + -3 = 8 Reorder the terms: -3 + -1x = 8 Solving -3 + -1x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 8 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 8 + 3 -1x = 8 + 3 Combine like terms: 8 + 3 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| 2z+6+3z=-34 | | 5(x+1)=40 | | 5g=2h-6 | | 2(4x-3)-8-2x=4 | | -9+12+4(3x-3)=7(x-2)-4x+14 | | 2(x-4)-3x=-4(x+2)+3x | | x^4+10x^2-299=0 | | 4y-8-2y=2-(-2) | | -(8(0)+4)=4(0)-2(6(0)+2) | | 4x^2-20xy-7x+35y= | | 3x^2+23x-8= | | 3(x+2)-2=6(x+1)-3x | | 4y-8-27=2-(-2) | | 14x-79=8x-25 | | 4x-(x+3)=6 | | -10+5y-35=-4 | | -10+5-35=-4 | | 7a-b=15 | | 175=85+(15+8)w | | (x-78)+x=180 | | 3b-12=6b-8 | | m+1=-1+3m | | -4y+36=4(3y-3) | | 5x-1x=15 | | 3.4x+5=22 | | 2.5x+2.5=12.5 | | 2.1(a+0.5)=-2.1(a+20) | | -5t-7t=2t | | -5x-24=2x+11 | | 5(c-1)-2(c+3)-2c=-8 | | 23=-3m+2 | | 11-4z=-27 |